2013
DOI: 10.1118/1.4835475
|View full text |Cite
|
Sign up to set email alerts
|

A Fano cavity test for Monte Carlo proton transport algorithms

Abstract: Using conservative user-defined simulation parameters, both PENH and Geant4 pass the Fano cavity test for proton transport. Our methodology is applicable to any kind of charged particle, provided that the considered MC code is able to track the charged particle considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 31 publications
1
26
1
Order By: Relevance
“…The choice of MC simulations parameters is important to get realistic dose deposition in small air cavities. Results of previous work on the Fano test drove the choice of setCutInRegion, dRoverRange, and finalRange parameters for protons. The setCutInRegion parameter is sensitive to get accurate stopping power ratios at z ref , especially for protons and electrons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of MC simulations parameters is important to get realistic dose deposition in small air cavities. Results of previous work on the Fano test drove the choice of setCutInRegion, dRoverRange, and finalRange parameters for protons. The setCutInRegion parameter is sensitive to get accurate stopping power ratios at z ref , especially for protons and electrons.…”
Section: Resultsmentioning
confidence: 99%
“…MC simulations are widely used to compute ionization chamber response in radiation beams. Sterpin et al showed that Geant4 is reliable for ionization chamber proton dose calculation using appropriate settings. Quality correction factors could be measured or obtained from MC simulations as follow:normalknormalQnormalA,normalQnormalB=normalDnormalwtrueDfalse¯airnormalQnormalAnormalDnormalwtrueDfalse¯airnormalQnormalBnormalWnormalairenormalQnormalAnormalWnormalairenormalQnormalBIf Q A and Q B are proton beams, the mean energy to create an ion pair in air, W air /e can be simplified andnormalknormalQnormalA,normalQnormalB=normalDnormalwtrueDfalse¯airnormalQnormalAnormalDnormalwtrueDfalse¯airnormalQnormalB…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of electron transport algorithms has been validated in several MC codes, such as EGSnrc, PENELOPE Geant4 . Sterpin et al, have designed a Fano cavity test for proton transport using Geant4 and PENH (PENELOPE extended to protons). Both codes were found to pass the Fano cavity test within 0.1% by using small step sizes.…”
Section: Introductionmentioning
confidence: 99%
“…penh is an extension of the Monte Carlo code penelope that includes the transport of protons based on their electromagnetic interactions in matter. Proton nuclear interactions and prompt‐gamma emission are included for a limited number of isotopes: 1H, 12C, 14N, 16O, 31P, 40Ca.30 Both penelope and penh have been reported to pass the Fano test within 0.1% for the energy range of interest to this work. Furthermore, penh has been shown to yield kQ factors in proton beams in good agreement with experimental data .…”
Section: Methodsmentioning
confidence: 99%